Low-grade inflammation during the glucocorticoid withdrawal phase in patients with Cushing's syndrome. Issue 4 (27th March 2023) - Vogel, Frederick; Braun, Leah; Zopp, Stephanie; Nowak, Elisabeth; Schreiner, Jochen; Benz, Irina; Rubinstein, German; Künzel, Heike; Ritzel, Katrin; Kroiss, Matthias; Honegger, Jürgen; Beuschlein, Felix; et al.
Abstract: Importance: Endogenous Cushing's syndrome (CS) leads to profound immunosuppression. Successful surgery induces biochemical remission and reversal of immunosuppression, which is characterized by clinical signs of glucocorticoid withdrawal and associated with increased susceptibility to infections and thromboembolic complications. Objective: We hypothesized that the glucocorticoid withdrawal phase is characterized by low-grade inflammation that may be related to patient-relevant outcomes. Setting: In this retrospective observational study, we analyzed longitudinal data from 80 patients with CS prospectively enrolled in the German Cushing's registry between 2012 and 2021. All enrolled patients underwent successful surgery. In a second step, a case–control study was performed in 25 of the patients with age-, gender-, and body mass index–matched control patients in whom hypercortisolism was excluded. Analyses included the inflammatory markers C-reactive protein and interleukin-6, as well as body composition, muscle function testing, and quality-of-life questionnaires. The patients were studied during active CS and in the postoperative remission phase 1, 3, 6, 12, and 24 months after surgery. Results: Compared with the preoperative phase and matched controls, patients with CS had increased systemic inflammatory markers in the early remission phase. One month following surgery, median (interquartile range) C-reactive protein was 0.48 mg dL −1 (0.14-0.90) vs 0.10 mg dL −1 (0.06-0.39) during active CS ( P ≤ .001). Similarly, interleukin-6 1 month after surgery was 7.2 pg mL −1 (3.3-11.7) vs 1.7 pg mL −1 (1.5-2.5) during active CS ( P ≤ .001). Obesity and hemoglobin A1c (HbA1c) were associated with increased inflammation levels. This proinflammatory state lasted until 1 year following surgery. Moreover, inflammatory markers during early remission showed an inverse correlation with long-term muscle function. Conclusions: The glucocorticoid withdrawal phase is associated with a low-grade inflammatory state, which is particularly pronounced in obese and hyperglycemic patients and related to lower muscle function.